The Relationship Between On the Job Training Flight Operation Officer and Job Readiness - Hadi Prayitno; Ekohariadi; Mochamad Cholik; Dhian Supardam; Wendra Dwiki Wibisono (International Journal of Science and Society, 2023)
On the Job Training Flight Operation Officer Relationship with Job Readiness. In this study there are two variables X (On the Job Training Flight Operation Officer), variable Y (Job Readiness) at PT Citilink Indonesia in Cengkareng City. The purpose of this study is to measure the relationship between, On the Job Training Flight Operation Officer PT Citilink Indonesia in Cengkareng City and job readiness of Indonesia Aviation Academy Banyuwangi (APIB) Cadets. The sampling technique in the study was carried out with the Solving formula with a sample of 38 cadets D-III Aircraft Operations Indonesia Aviation Academy Banyuwangi at PT Citilink Indonesia in Cengkareng City. Data analysis uses the pearson product moment correlation test which is used to test independent variables and dependent variables. Based on the results of data analysis using the pearson product moment method, a value of 0.881 with a significant value of 0.000 is less than 0.05 which means it has a very high and significant relationship between, On the Job Training Flight Operation Officer and job readiness. So, it can be concluded that On the Job Training Flight Operation Officer is very closely and significantly related to job readiness.